Admixtures for concrete : proceedings of the International Symposium held by RILEM (The International Union of Testing and Research Laboratories for Materials and Structures) and organized by RILEM Technical Committee TC-84AAC and Departmento de Ingenieria de la Construccion Escuela Tecnica Superior de Ingenieros de Caminos, Canales y Puertos Universitat Politécnica de Catalunya, Spain, Barcelona, May 14-17, 1990 /: proceedings of the International Symposium held by RILEM (The International Union of Testing and Research Laboratories for Materials and Structures) and organized by RILEM Technical Committee TC-84AAC and Departmento de Ingenieria de la Construccion Escuela Tecnica Superior de Ingenieros de Caminos, Canales y Puertos Universitat Politécnica de Catalunya, Spain, Barcelona, May 14-17, 1990. (1990) - Unknown
No abstract available